1988
DOI: 10.1016/0741-5214(88)90379-5
|View full text |Cite
|
Sign up to set email alerts
|

The use of preoperative exercise testing to predict cardiac complications after arterial reconstruction

Abstract: To assess the value of exercise testing in the prediction of cardiac risk, 100 patients requiring arterial reconstructive surgery had either treadmill testing or arm ergometry before operation. Thirty-four patients then had abdominal aortic aneurysm repair, 48 had reconstructions for aortoiliac occlusive disease, and 18 had infrainguinal revascularization procedures. Cardiac complications included myocardial infarction in 10%, acute congestive failure in 5%, malignant ventricular arrhythmias in 7%, and cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
2

Year Published

1989
1989
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(50 citation statements)
references
References 13 publications
0
48
0
2
Order By: Relevance
“…The risk of perioperative cardiac events and long-term risk are increased significantly in patients with an abnormal exercise ECG at low workloads. 176,178,179 In contrast to the above-mentioned studies of patients with vascular disease, in a general population of patients in which only 20% to 35% had peripheral vascular disease and who were undergoing noncardiac surgery, Carliner et al 185 reported exercise-induced ST-segment depression greater than or equal to 1 mm in 16% of 200 patients older than 40 years (mean age 59 years) being considered for elective surgery. Only 2 patients (1%) had a markedly abnormal (ST-segment depression of 2 mm or more) exercise test.…”
Section: Exercise Stress Testing For Myocardial Ischemia and Functionmentioning
confidence: 92%
See 1 more Smart Citation
“…The risk of perioperative cardiac events and long-term risk are increased significantly in patients with an abnormal exercise ECG at low workloads. 176,178,179 In contrast to the above-mentioned studies of patients with vascular disease, in a general population of patients in which only 20% to 35% had peripheral vascular disease and who were undergoing noncardiac surgery, Carliner et al 185 reported exercise-induced ST-segment depression greater than or equal to 1 mm in 16% of 200 patients older than 40 years (mean age 59 years) being considered for elective surgery. Only 2 patients (1%) had a markedly abnormal (ST-segment depression of 2 mm or more) exercise test.…”
Section: Exercise Stress Testing For Myocardial Ischemia and Functionmentioning
confidence: 92%
“…In most series, very-highrisk patients (recent MI, unstable angina, HF, and serious ventricular arrhythmias) were excluded. McPhail et al 176 reported on preoperative exercise treadmill testing and supplemental arm ergometry in 100 patients undergoing surgery for peripheral vascular disease or abdominal aortic aneurysm. Of the 100 patients, 30 were able to reach 85% of agepredicted heart rate maximum, and only 2 had cardiac complications (6%).…”
Section: Exercise Stress Testing For Myocardial Ischemia and Functionmentioning
confidence: 99%
“…66-67 Patients able to achieve greater than 85 per cent of their predicted maximum heart rate at high maximal oxygen uptake may represent a low risk group for major vascular surgery. 68 The ability of vascular surgery patients to participate in exercise studies may be hampered by claudication, arthritis and amputation while digitalis, diuretic and beta-blocking agent administration may cause difficulties of interpretation. 69 In addition, limited sensitivity and low specificity have been reported for exercise testing.…”
Section: Non-invasive Assessmentmentioning
confidence: 99%
“…An important limitation of this test in perioperative evaluation for noncardiac surgeries is the fact that 30% to 50% of the patients referred to the cardiologist for preoperative evaluation for major or vascular surgeries cannot achieve sufficient load during exercise to assess cardiac reserve [37][38][39] .…”
Section: Exercise Stress Testingmentioning
confidence: 99%